Effect of sun exposure on hypopigmented and hyperpigmented nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
With regard to sun exposure mothers usually pay greater attention to hypopigmented nevus. In contrast with vitiligo, the skin of hypopigmented nevus does not redden or burn more than normal skin and often gets tanned more than normal skin (3), so that the difference between healthy and nevus skin is more evident on the covered skin than on the skin exposed to sun radiations. Therefore, the skin of hypopigmented nevus should not be protected with sunscreens. On the other hand, when it gets tanned more than normal skin, sun exposure of the nevus should be encouraged. In the latter case adolescents could expose the nevus to artificial UV before sun exposure in order to reduce the esthetical impact in the first days on the beach. With regard to hyperpigmented nevus, although there is no risk of sun burning, the amount of sun radiation on the hyperpigmented skin should be reduced as compared with the healthy surrounding skin, in order to prevent its greater visibility during summertime.